PATIENTS SHOULD BE ACTIVE PARTICIPANTS IN GRAND ROUNDS BUT ARE STUDENTS READY?. Issue 12 (15th November 2016) - Schon, Frederick; Cock, Hannah; Mistry, Jayna
Abstract : A major way of teaching clinical neurology has been to elicit histories and signs of neurological patients in front of large groups of medical students or neurology trainees. Traditionally at this point the patient leaves after which the diagnosis and management is discussed. Patients however are increasingly partners in their care planning. This questionnaire study has compared how students and patients feel about patients being present throughout case demonstrations. Between 2013–2015 after each weekly "case demonstration" patients were given an anonymous questionnaire to fill in ( total 66), whilst students were given a matched questionnaire at the end of their 5 week attachment ( total 153). Patients expressed high levels of satisfaction with all aspects of the sessions, most importantly 98% (40/41) specifically said they were pleased they stayed throughout the session rather than leaving after just the history and examination. In sharp contrast 53% of students expressed doubts about patients staying and 63% felt patients were either not comfortable or well treated in the sessions. When given the opportunity to comment freely, 19% (29/153) students specifically expressed their reservations about patients staying for the discussion. 59% (30/51) of students who said that they themselves did not feel comfortable during the sessions. This study asks if the traditional "case demonstration" needs to change to include the modern patient's role. Patients were massively in favour whilst students had major reservations. The increasing use of actors, videos and role play may make students less ready for such direct patient involvement.